Niektóre nowe metody badania struktury i dynamiki procesów demograficznych Niemieckiej Republiki Demokratycznej - Zając, Kazimierz; Grabiński, Tadeusz (Wydział Prawa i Administracji UAM, 1975)
The purpose: of this paper is to present some numerical methods for objective determination of more homogeneous phases in demographic processes in GDR. from 1947 to 1973. Periods described by 12 attributes are the subject of discrimination. Such an approach opens new possibilities in time series analyses. Several taxonomie algorithms were used, along with two completely new numerical methods. Using these methods, the authors mark out substantially different phases in the development of demographic processes in GDR.
Some New Methods in Research of the Structure and Dynamics of the Demographic Process in the GDR